Butterflies Across the Globe: A Synthesis of the Current Status and Characteristics of Monarch (Danaus plexippus) Populations Worldwide - Nail, Kelly R.; Drizd, Lara; Voorhies, Kristen J. (Frontiers in Ecology and Evolution, 2019)
Recent declines in the migratory North American populations of monarchs (Danaus plexippus) have necessitated efforts to evaluate the current status of the species, including worldwide populations. While monarchs originate from North America and may be ancestrally migratory, they have expanded throughout many parts of the world over the past 200 years. Most of these newer populations no longer migrate and face a variety of threats across a wide range of habitats, but we lack a comprehensive review of locations and characteristics of these worldwide populations. We thus delineated the current range of monarchs and their status throughout the world, recording over 90 countries, islands, and island groups where monarchs occur (74 with recent documented sightings) and known features of these populations. We discuss the major differences between these populations, focusing on morphology, migration, overwintering, natural enemies, larval diet, and genetics. The differences documented here provide the species with adaptive capacity, thus better allowing the species to adapt to novel changes in its environment. We end with a discussion of current gaps in our understanding of monarchs worldwide and directions for future research.